Multimedia Technologies in the Educational Process of Higher Education - Samigova G. A. (Researchparks Publishing, 2022)
This article describes the features of the use of multimedia technology in education. The article analyzes the use of multimedia technologies in teaching university students, and suggests ways to improve the efficiency of using modern technologies in the learning process.